Fin Efficiency of Serrated Fins : 3rd Report, Correction Factor for the Theoretical Fin Efficiency - HASHIZUME, Kenichi; MORIKAWA, Ryo; KOYAMA, Tetsuya; MATSUE, Takahiro (Nihon Kikai Gakkai rombunshuu. B hen, 2000)
A correction factor for the theorectical fin efficiency of serrated fins was derived from an experiment. This correction factor compensates the influence of the assumptions made in the analytical model used for evaluating the fin efficiency, which has been derived theoretically in the 1st report of our atudy and has been expressed as an approximate equation in the 2nd report. Using this correction factor together with the theoretical fin efficiency, the actual fin efficiency can be estimated for serrated fins of various fin geometries, including plain or solid fins.